Analisis Efektivitas Pemeriksaan Pajak dan Implementasi Sistem Pelaporan Pajak Online terhadap Kepatuhan Wajib Pajak di Indonesia - Tarmizi Ali; Moch Kurniawan Adli; Dwi Anggi Syaputra (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
This study aims to analyze the effectiveness of tax audits and the implementation of online tax reporting systems (e-filing and e-reporting) on taxpayer compliance in Indonesia. Tax audits serve as a supervisory instrument conducted by the Directorate General of Taxes to ensure that tax obligations are fulfilled in accordance with applicable regulations. On the other hand, technological advancements have driven the modernization of tax administration through the adoption of online reporting systems, which aim to enhance convenience and transparency. This research uses a quantitative approach with survey methods targeting individual and corporate taxpayers registered at several tax service offices (KPP) across Indonesia. The findings indicate that properly conducted and periodic tax audits have a significant impact on improving taxpayer compliance. Moreover, the online reporting system has proven effective in increasing efficiency, reducing compliance costs, and enhancing transparency, thereby positively influencing voluntary compliance. The study concludes that the synergy between effective tax audits and a user-friendly online reporting system is a strategic key to improving tax compliance in Indonesia.